Start with Why: How Great Leaders Inspire Everyone to Take Action - Simon Sinek (London Portfolio/Penguin, 2014)
Why are some people and organizations more innovative, more influential, and more profitable than others? Why do some command greater loyalty? In studying the leaders who've had the greatest influence in the world, Simon Sinek discovered that they all think, act, and communicate in the exact same way-and it's the complete opposite of what everyone else does. People like Martin Luther King Jr., Steve Jobs, and the Wright Brothers might have little in common, but they all started with why. Drawing on a wide range of real-life stories, Sinek weaves together a clear vision of what it truly takes to lead and inspire.
Keywords: Business; Leadership; Nonfiction; Self Help